WHAT IS PLAGIARISM? - Ahmatova Mohichexra Mo‘minjon qizi (Ustozlar uchun, 2025)
Abstract: This article provides a comprehensive analysis of plagiarism, exploring its definition, various forms, consequences, and prevention strategies within academic contexts. It examines the ethical and legal implications of plagiarism, with a particular focus on its impact on scholarly integrity and societal progress. The article also addresses the growing issue of plagiarism in Uzbekistan, highlighting local efforts to combat it and drawing on international best practices. Designed for researchers, students, and educators, this work aims to foster a deeper understanding of plagiarism’s detrimental effects and promote strategies to uphold academic integrity.